Esses alemão tem que se convencer que não mandam mais na cidade...: relações entre sociedade receptora e (i)migrantes em Panambi na década de 1970 - Mello, Eliane de (Universidade do Vale do Rio do Sinos, 2006)
This study has as objective to analyze the relationships between receiver society and migrants, in particular the ones that refer to the incorporation of new inhabitants to the place of destination. Therefore, it was taken empirical objective the relationships established between these two groups in the town called Panambi, located in the northwest region of Rio Grande do Sul, in the decade of 1970. Formed by German and Portuguese-Brazilian (im)migrants/descendents, the above-mentioned place lived a conflicting process of identity construction, which resulted on a supposed economic, cultural and political hegemony of the German ethnic group. However, in the decade of 70, its quick economic development caused the destabilization of this structure, in particular due to the mass migration. Among the consequences of this process was the widening of the ditch between wealthy and poor people, the changes on the physical structure of the town, and the beginning of the old systems of values and customs disintegration
Keywords: História social; Panambi; Rio Grande do Sul; imigração alemã; Ciências Humanas